Implementasi Kebijakan Pengelolaan dan Pengusahaan Sarang Burung Walet di Kota Pekanbaru - Rinaldy May Wendra; Teuku Afrizal; Eko Supriyono; Siauw Tiffani Setiono; Annisa Nurfitriani Fatimah (PERSPEKTIF, 2020)
The policy on management and management of swallow nests aims to regulate the management and management of swallow nests in order to contribute to the community and local government. This policy was outlined in Pekanbaru City Regulation Number 3 of 2007 concerning Business Permit for the Management and Management of Swallow's Nest. Several problems arise, among others, the number of business licenses that are still very minimal which has an impact on the contribution of regional income, noise pollution, air pollution, environmental impacts and health problems. This study aims to analyze the implementation of management policies and management of swallow's nests in Pekanbaru City. This research uses a qualitative descriptive approach through literature study. Analysis of policy implementation is seen through the Edward III model, which pays attention to the effectiveness of implementation in terms of communication, resources, disposition and bureaucratic structure. The results of the study concluded that the implementation of the management and management policy for swallow nests has not run effectively. In controlling the swallow breeding business permit, there are many obstacles, among others, coordination between related agencies that has not been running well, supervision by related agencies which is still very low, low levels of employer compliance due to sanctions that have never been applied, so there needs to be an evaluation of policies when this is by paying more attention to environmental impacts and firmer sanctions.